Remedial Programme in Fractions for Primary School Students - Ran, Rekha (THE PRIMARY TEACHER, 2016)
An area in arithmetic that is, particularly, difficult for students is understanding the concept of fractions. They may feel embarrassed when problems related to fractions persist later in their lives. For teachers, it becomes difficult to remediate the misconceptions of the students in regular classrooms, particularly, when the concept is as challenging as the concept of fractions. The teachers must have at hand effective instructional procedures, material and other resources to teach mathematics to the students having conceptual problems in fractions based on the assumption that all can learn. The objective of this paper is to provide the teachers with best practices for teaching fractions to primary school students.